Default mode network connectivity of fear- and anxiety-related cue and context conditioning - Zidda, Francesca; Ruttorf, Michaela; Flor, Herta (NeuroImage, 2018)
Classical fear conditioning is an important mechanism to adequately respond and adapt to environmental threats and has been related to the development of fear and anxiety. Both cue and context conditioning have been studied but little is known about their relation to relevant resting state networks. The default mode network (DMN) has been reported to be involved in affective learning and described as facilitating a state of readiness in responding to environmental changes. We examined resting state brain connectivity patterns of the default mode network (DMN) in 119 healthy volunteers. Specifically, we carried out correlation analyses between the DMN and skin conductance responses (SCRs) as well as arousal, valence and contingency ratings during learning. In addition, we examined the role of trait anxiety. Two different DMN patterns were identified in which stronger connectivity was linked to lower differential SCRs during fear and anxiety learning. One was related to cue conditioning and involved the amygdala and the medial prefrontal cortex, and one was associated with context conditioning and included the hippocampal formation and sensorimotor areas. These results were replicated in an independent sample. Functional connectivity of the DMN with these key regions at rest was also predictive of trait anxiety but this association could not be replicated in the second sample. We showed that DMN connectivity is differently associated with cued versus contextual learning mechanisms. Uncovering individual differences in baseline network connectivity of the DMN with these key regions might lead to a better understanding of fear and anxiety. Such findings could indeed help to identify vulnerability factors linked to network alterations at rest with dysregulation of learning processes involved in the pathophysiology of stress and anxiety disorders.